Qur’anic Revelation: The Comparison between the Methods of Tafsir and Fiqh in its Interpretation - Yusuf Olawale Owa-Onire Uthamn (Indonesian Journal of Islamic Literature and Muslim Society, 2023)
This research article delves into the significance of understanding the accurate interpretation of the sacred scripture, the Qur'an, as a religious priority for Muslims. It asserts that it might be an obligatory duty for Islamic scholars to exhibit a profound knowledge of this revered text. The study begins by introducing key terminologies, including Quranic revelation (Wahy), its exegesis (tafsir), and Qur'anic interpretation (ta'wil). These technical terms are elucidated to facilitate a straightforward comparison between the methodologies employed in the fields of tafsir (Qur'anic commentary) and fiqh (Islamic jurisprudence) for interpreting the Qur'an. The research comprehensively investigates the subject matter and the aforementioned terms by employing an analytical approach. To ensure the rigor of the research, various documented materials such as books, journal articles, and manuscripts related to the field of Qur'anic science and its interpretation have been consulted. This study aims to contribute to a deeper understanding of the importance of interpreting the Qur'an accurately and the methods employed in its interpretation within the context of Islamic scholarship.